ENGLISH READING INTEREST ANALYSIS ON GENSHIN IMPACT GAME STORYLINE - Duhita, Fajar Ratna; Syahbana, Kayla Maghfi; Subagyo, Muhammad Akbar; Melati, Pramesti Dewi Sekar; Nirmala, Nirna; Hamid, Syifa Fadhilah (PRIMACY Journal of English Education and Literacy, 2024)
This research intends to analyze the reading interest of Genshin Impact game players. This research aims to make people more interested in increasing their interest in reading. Because, interest in reading in Indonesia is very low, according to UNESCO data, there is only 0.001% interest in reading in Indonesia. This is certainly a big concern for researchers. Researchers took this case for a study because researchers also want to prove how many online game players have increased their interest in reading because of playing online games, one of which is the Genshin Impact game. Based on the research, the respondents fully believe that they get a lot of positive impacts from playing the Genshin Impact game; get new vocabulary, get lessons from the Genshin Impact storyline, know how to pronounce words correctly from the style of speech to the accent uttered by a Genshin Impact game character. The respondents also admitted that not only did they have fun playing the game, but they also got very good learning.